Positive allosteric modulators of α7 nicotinic acetylcholine receptors affect neither the function of other ligand- and voltage-gated ion channels and acetylcholinesterase, nor β-amyloid content - Arias, Hugo R. (2016)
tThe activity of positive allosteric modulators (PAMs) of 7 nicotinic acetylcholine receptors (AChRs),including 3-furan-2-yl-N-p-tolyl-acrylamide (PAM-2), 3-furan-2-yl-N-o-tolylacrylamide (PAM-3), and3-furan-2-yl-N-phenylacrylamide (PAM-4), was tested on a variety of ligand- [i.e., human (h) 7, rat(r) 910, h3-containing AChRs, mouse (m) 5-HT3AR, and several glutamate receptors (GluRs)] andvoltage-gated (i.e., sodium and potassium) ion channels, as well as on acetylcholinesterase (AChE) and-amyloid (A) content. The functional results indicate that PAM-2 inhibits h3-containing AChRs(IC50= 26 ± 6 M) with higher potency than that for NR1aNR2B and NR1aNR2A, two NMDA-sensitiveGluRs. PAM-2 affects neither the activity of m5-HT3ARs, GluR5/KA2 (a kainate-sensitive GluR), nor AChE,and PAM-4 does not affect agonist-activated r910 AChRs. Relevant clinical concentrations of PAM-2?4 do not inhibit Nav1.2 and Kv3.1 ion channels. These PAMs slightly enhance the activity of GluR1 andGluR2, two AMPA-sensitive GluRs. PAM-2 does not change the levels of A42in an Alzheimer?s diseasemouse model (i.e., 5XFAD). The molecular docking and dynamics results using the h7 model suggest thatthe active sites for PAM-2 include the intrasubunit (i.e., PNU-120596 locus) and intersubunit sites. Theseresults support our previous study showing that these PAMs are selective for the 7 AChR, and clarifythat the procognitive/promnesic/antidepressant activity of PAM-2 is not mediated by other targets.